2016
DOI: 10.1002/2015ja021968
|View full text |Cite
|
Sign up to set email alerts
|

EMIC waves observed at geosynchronous orbit under quiet geomagnetic conditions (Kp ≤ 1)

Abstract: We statistically study the local time distribution of the helium band electromagnetic ion cyclotron (EMIC) waves observed at geosynchronous orbit when geomagnetic activity was low (Kp ≤ 1). In order to identify the geosynchronous EMIC waves, we use high time resolution magnetic field data acquired from GOES 10, 11, and 12 over a 2 year period from 2007 and 2008 and examine the local time distribution of EMIC wave events. Unlike previous studies, which reported high EMIC wave occurrence in the postnoon sector w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
81
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(97 citation statements)
references
References 40 publications
(78 reference statements)
16
81
0
Order By: Relevance
“…For C3 category, He + band EMIC waves are predominantly observed with wide spatial coverage at 3–14 MLT and at L ∼4–6.5, while there are significantly lower H + band EMIC wave occurrence rates (Figure c). The peak occurrence rate of C3 near the noon sector is consistent with previous studies of EMIC wave occurrence rates during steady quiet geomagnetic conditions at geosynchronous orbit (e.g., Kim et al, ; Park et al, ). The wider L shell coverage of He + band wave might be related to the influence of the expanding plasmasphere during quiet geomagnetic conditions (Kwon et al, 2015).…”
Section: Statistical Resultssupporting
confidence: 90%
“…For C3 category, He + band EMIC waves are predominantly observed with wide spatial coverage at 3–14 MLT and at L ∼4–6.5, while there are significantly lower H + band EMIC wave occurrence rates (Figure c). The peak occurrence rate of C3 near the noon sector is consistent with previous studies of EMIC wave occurrence rates during steady quiet geomagnetic conditions at geosynchronous orbit (e.g., Kim et al, ; Park et al, ). The wider L shell coverage of He + band wave might be related to the influence of the expanding plasmasphere during quiet geomagnetic conditions (Kwon et al, 2015).…”
Section: Statistical Resultssupporting
confidence: 90%
“…This distribution characteristic is consistent with results from Park et al []. The reason for this kind of distribution is suggested to be related to dawn‐dusk asymmetric response to enhancement of solar wind dynamics [ Park et al , , ].…”
Section: Summary and Discussionsupporting
confidence: 91%
“…Park et al . [] found a similar pattern in their study of EMIC waves observed during geomagnetically quiet conditions at geosynchronous orbit: the mean and 75th percentile values of Psw increased shortly before wave onset but not the 25th percentile values.…”
Section: Superposed Epoch Analysismentioning
confidence: 98%
“…This local time range is consistent with the observations of Park et al . [] at geosynchronous orbit that quiet time EMIC waves (including those during isolated compressions) mostly occurred on the dayside with a peak occurrence near noon.…”
Section: Statistical Studymentioning
confidence: 99%